Perubahan Formula Harga Patokan Mineral dan Implikasinya terhadap Nilai Ekonomi Mineral Ikutan pada Bijih Nikel : Changes in the Mineral Reference Price Formula and Their Implications for the Economic Value of Associated Minerals in Nickel Ore - Mahader; Wd Rizky Awaliah Nafiu; Erwin Anshari (Journal of Engineering Science and Technology Applications, 2026)
This study aims to identify associated elements in nickel ore and estimate their economic value in the stockpile area of PT. Z, South Konawe Regency. A quantitative approach was applied using photogrammetric data, material density, moisture content, X-Ray Fluorescence (XRF) assay results, and benchmark mineral prices for July 2026. The volumes of seven stockpiles (NDJ 1–NDJ 7) were determined through three-dimensional modelling and converted into tonnage using a material density of 1.6 t/m³. The estimated economic value was calculated using the Mineral Reference Price (HPM) formulation stipulated in Ministerial Decree of Energy and Mineral Resources No. 144.K/MB.01/MEM.B/2026 and compared with the formulation under Decree No. 268.K/MB.01/MEM.B/2025. XRF results indicated Ni grades of 1.54%–1.73%, Fe 11.71%–18.41%, Co 0.030%–0.062%, and Cr 0.595%–1.197%. The total stockpile material amounted to 501,192.0 WMT. The estimated economic value based on the 2026 HPM formulation reached USD 38,314,418.4, compared with USD 19,233,221.8 under the 2025 formulation, resulting in an estimated difference of USD 19,081,196.6. The findings indicate that the revised HPM formulation results in a higher estimated economic value of the stockpile material by incorporating qualifying associated elements into mineral valuation.